PLACE, ROLE AND FEATURES OF CRITICAL THINKING IN THE PROTECTION OF MILITARY PERSONNELS IN THE INFORMATION SPACE (TAMADDUN NURI JURNALI, 2024)
The main aim of work is to create new methods of evaluation system of critical thinking level and critical thinking progress against negative information psychologic influence on military personnel. In this article degree work developed and successfully tested on practice evaluation system of protecting level against negative information psychologic influence on military personnel and evaluating psychologic methods.